Adropin and Preptin Levels in β-Thalassemia Major Complications in Babylon Province - Zinah Abbass Ali; Samar Hasan Shammar (Medical Journal of Babylon)
Background: Thalassemia refers to a group of diseases in which one or more globin chains are produced less or not at all, causing a wide range of phenotypes from anemia to clinically asymptomatic individuals. Disturbances in the homeostasis of carbohydrates, serum lipids, and oxidative stress are the most common diseases brought on by iron overload in beta-thalassemia major (β-TM). Objective: To examine the association of biochemical parameters with β-TM complications in Babylon Province. Materials and Methods: This study involved 100 individuals, separated into two groups: 50 subjects and 50 controls. Commercial enzyme-linked immunosorbent assay kits were used to measure cystatin-C, ferritin, insulin, preptin, and adropin, while serum blood urea (B. urea), serum creatinine (S.Cr), and lipid profile along with fasting glucose concentration were calculated by colorimetric kit using the spectrophotometer method. Results: Serum samples were used to measure biochemical parameters of S.Cr, urea, cystatin-C, ferritin, fasting insulin, fasting glucose, adropin, preptin, and lipid profile. Adropin in the patient group of thalassemia was significantly decreased compared to the healthy controls (P < 0.001). However, preptin, cystatin-C, ferritin, B. urea, and S.Cr were elevated in the patient groups compared to the control group (P < 0.005). Also, the lipid profile, including triglycerides, cholesterol, high-density lipoprotein, low-density lipoprotein, and very low-density lipoprotein, showed significant differences between patient group of thalassemia and the control group. Conclusion: Adropin and preptin were considerable predictive markers for the development of complications in patients with β-TM.